Vitamin D deficiency and intracranial aneurysms: Systematic Review - Lívio Pereira de Macêdo; Glaudir Donato; Maria Eduarda d’Almeida Lins Regis; Isabela Fernandes de Melo Pereira; Gustavo Rodrigues Paulo; Kamilla Azevedo Bringel; Gabriel Carvalho Andrade Gadelha; Fábio Antônio Serra de Lima Júnior; Yally Dayanne Oliveira Ferreira; Renata de Castro Tavares; Arlindo Ugulino Netto; Kauê Franke; et al. (World Neurosurgery: X)
Background: Low vitamin D levels have been associated with an increased risk in patients with cerebrovascular diseases. However, solid evidence linking intracranial aneurysm (IA) to hypovitaminosis D is still lacking. This review aims to evaluate if there is a relationship between vitamin D deficiency and the incidence and rupture of IA. Methods: A systematic search of papers was performed in the following databases: MEDLINE, EMBASE, LILACS, and Web of Science. The selected papers covered data on vitamin D levels and the occurrence or rupture of IA and/or other complications of this condition. The risk of bias analysis was performed with tools developed by the National Heart, Lung, and Blood Institute. Tables were developed to synthesize the qualitative analysis of the data. Results: Six studies from five different countries were included covering a total of 14,184 participants. A relationship between low vitamin D levels and IA incidence was detected in all studies. In terms of rupture and complications, there was a tendency of association with hypovitaminosis. Discussion: Among the limitations of the papers, the following are noteworthy: sample size and selection, recording flaws inherent to retrospective designs, failure to consider confounding variables, and heterogeneity of data produced among the researches, making a quantitative analysis of the evidence unfeasible. From the results obtained, we can identify a higher incidence of hypovitaminosis D in patients with IA. Yet, further studies need to be conducted in investigating the relationships between low vitamin D levels and rupture or other complications (CRD42022363369).